Analyzing the hardness and wear properties of SiC and hBN reinforced aluminum hybrid nanocomposites. (2022) - Krishnan, Parthiban; Lakshmanan, Poovazhagan; Palani, Sarangapani; Arumugam, Arun; Kulothungan, S.
Abstract: Hybrid composites based on aluminum have become more popular in a variety of sectors for decades, with various reinforcements incorporated to improve wear resistance properties. The intention of this work is to inspect the hardness and dry sliding wear properties of a novel metal matrix hybrid nanocomposite of Al6063-5% SiC-x wt% hBN (x = 0.5%, 1.5% and 2.5 wt%) fabricated by ultrasonication assisted stir casting method. The investigational results indicated that the insertion of secondary hBN particles greatly enhanced the wear characteristics of the hybrid composite because of the self-lubricating properties of hBN. The Vickers hardness test is used to determine the hardness of the composites, and it demonstrates the increased hardness. SEM microscopy was used to analyze the microstructures, material combinations, wear, and friction features. By using a pin on a disc tribometer, wear characteristics of Al6063 and Al6063 + SiC/hBN were studied for loads 40–80 N, distance 1000 m, and velocity 1 m/s. Nanocomposites yield superior hardness and wear resistance properties over monolithic alloys. The composition of 5% SiC and 1.5% hBN reinforced nanocomposites shown maximum improvement in hardness and wear resistance properties.